The Concept of Moral Education for Children According to Kitab Tarbiyatul Aulad - Muhammad Nuur Hidayah (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2022)
The study aims to describe the concept of moral education in children according to the book tarbiyatul aulad from Abdullah Nashih Ulwan as a guide in educating children in the present day that moral decline has taken place. This study is of literature research by collecting and analyzing the data sources of the various books, journals and documents relating to the educational thought of abdullah nashih ulwan. The study congcluded that material of moral education that abdullah nashih ulwan offers, that are, the moral education in  the family and in the environment. In teaching morals, Abdullah Nashih Ulwan provided several methods such as teaching, habituation, punishment and reward and also giving good advice.